Declaratoria de perención en el contexto administrativo como forma anormal de terminación del proceso. Análisis desde el decreto 01 de 1984 y el Cpca –ley 1437 de 2011- (2016)
The public end of any process or litigation consists of dissolving conflicts and of sol- ving the judgments across a judgment, for it before the problem that one presents in the judicial Colombian system, where the processes remain indefinite time in the courts, good is for inertia of the parts in conflict or for negligence of the judge to pronounce, which generates disturbance in the social, juridical and economic peace of the collectivity, it proposes in this investigation to analyze the declaration of expiration as abnormal form of completion of the administrative process, realizing an analysis from in previous Contentious Administrative Code and the in force CPACA.This way, from the article 54 of the Law 105 of 1890, rule that was regulating the caducity of the instance - Perención - for abandon of the actor, has come being fa- miliar the topic in our right, as which the Law 105 of 1931, the current Code of Civil Procedure, the Contentious Administrative Code (Statutory order 01 of 1984 and Law 1437 of 2011) and the Jurisprudence they have dealt with him.